PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), RETURN ON ASSETS (ROA), DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM (Studi pada Perusahaan Sub Sektor Telekomunikasi yang Terdaftar di Bursa Efek Indonesia Periode 2013-2016) - Riris Novitasari; Apriatni EP (Jurnal Ilmu Administrasi Bisnis, 2017)
Telecommunication that researcher works at consists of 4 companies. In the last four years, the average price of sub sector of telecommunication shares in the period 2013-2016 has increased but if we look at the stock price obtained by each company, we will see that there are companies in the sub sector of telecommunication continues to decline stock price during the period 2013-2016. The condition of stock price which has been decreasing is the concern for the researcher to review the financial condition of the telecommunications company. This type of research is explanatory research, with population that can be studied in 4 companies sub sector of telecommunication. The data source of the research is the secondary data obtained not direct. The data types used in this research are time-series data and cross section data or often referred to as panel data. Methods of data analysis used classical assumption test, correlation, determination, simple regression, multiple regression, and significance by using SPSS application. The result of research stated that ROA and ROE have an effect on stock price, which means that if ROA and ROE increase, stock price increases partially. While CR and DER have no effect on stock prices. Testing simultaneously shows CR, DER, ROA, and ROE have an influence on stock prices. If CR, DER, ROA, and ROE increase, then stock price increases as well. Based on this, the researcher suggested that sub sector of telecommunication’s company pays attention to indicator on CR, DER, ROA, and ROE to increase stock price. So that investors are interested to invest in the company.